Модифицирование формулы амплитуд колебаний якоря электромагнитного вибровозбудителя - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
New formulas for the amplitude of rotor oscillations of an electromagnetic vibroexciter are deduced with regard for oscillations of an air clearance.